Dye-sensitized solar cell utilizing quasi one-dimensional of highly compact vertical array ZnO nanorod - Umar A.A.; Rahman M.Y.A.; Taslim R.; Salleh M.M. (2023)
Highly compact quasi one-dimensional ZnO nanorods was synthesized for dye-sensitized solar cell of FTO/ZnO/electrolyte/platinum. ZnO nanorods were grown on FTO substrate at room temperature via ammonia assisted rapid hydrolysis process technique. The sample was grown throughout the substrate by multi-growth process for about 5-30 minutes. ZnO nanorods were characterized by FESEM with vertical array oriented with the average diameter and length of 48 nm and 220 nm, respectively. The (cis-bis(isothiocyanato)bis(2,2'-dicarboxylato)-ruthenium(II) bis-tertabutylammonium) (N719) dye was coated on the samples and utilized in the cell to improve its performance. The cell performance was tested in dark and under illumination of 100 mWcm-2 light. The cell exhibits photovoltaic effect with the Jsc of 0.45 mAcm-2, Voc of 0.56 V and FF of 24%.